2021
DOI: 10.5603/rpor.a2021.0020
|View full text |Cite
|
Sign up to set email alerts
|

Real-time measurement of ICD lead motion during stereotactic body radiotherapy of ventricular tachycardia

Abstract: background: here we aimed to evaluate the respiratory and cardiac-induced motion of a IcD lead used as surrogate in the heart during stereotactic body radiotherapy (sBrT) of ventricular tachycardia (VT). Data provides insight regarding motion and motion variations during treatment. Materials and methods:We analyzed the log files of surrogate motion during sBrT of ventricular tachycardia performed in 20 patients. evaluated parameters included the IcD lead motion amplitudes; intrafraction amplitude variability; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…This is consistent with the findings of Knybel et al, who employed online tracking during treatment delivery and found that target motion exceeded 3 mm in 35% of their cases. 25 A central limitation of this study is reliance on DIR.DIR performance assessment is a subjective process which is dependent on user experience and can be subject to error without quality assurance (QA). The registration QA also needs to be specific to the underlying goal of the DIR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of Knybel et al, who employed online tracking during treatment delivery and found that target motion exceeded 3 mm in 35% of their cases. 25 A central limitation of this study is reliance on DIR.DIR performance assessment is a subjective process which is dependent on user experience and can be subject to error without quality assurance (QA). The registration QA also needs to be specific to the underlying goal of the DIR.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that motion is often non‐uniform, and it is reasonable to surmise a cardiac lead may either over or under‐estimate movement. Knybel et al have also shown that the lead can exhibit larger motion than the target area, and that the correlation between lead motion and target motion vary from patient to patient 25 . Both cardiac gating under voluntary breath hold and combined cardio‐respiratory gating have been shown to be feasible in preclinical studies, 26,27 and further investigation of these techniques may offer a way to reduce total cardio‐respiratory positioning uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…For our technology, it is, namely, LED marker correlation uncertainty. However, since in GDM-based volume, cardiac motion should be included, the same factor causing the increase in the correlation uncertainty ( 7 ) should not be included again. Again, for this reason, we decided to use a 2-mm isotropic margin overall.…”
Section: Discussionmentioning
confidence: 99%
“…Our treatment planning and delivery procedure have been described in detail previously ( 4 , 7 9 ). After initial development, the original target definition workflow was established as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Mean target displacements induced by respiration have been reported as 3.9 mm left/right, 4.1 mm anterior/posterior, and 4.7 mm superior/inferior. Additionally, these motions are highly patient-specific, depending on the location of the target in the heart and the respiration amplitude [4,5]. The main target motion management technique used in CR, especially when using a C-arm linear accelerator, is the generation of a cardiorespiratory internal target volume (ITV) based on cardiac-gated and/or respiration-gated four-dimensional computed-tomography (4D-CT) scans [3].…”
Section: Introductionmentioning
confidence: 99%